Hubungan Karakteristik, Pengetahuan Ibu, dan Dukungan Keluarga terhadap Keberhasilan ASI Eksklusif pada Bayi - Harahap, Maulana Muhammad Yusuf Zakaria; Wijaya, Johanna Fransiska (Pusat riset dan Inovasi Nasional, 2025)
Exclusive breastfeeding plays a crucial role in reducing neonatal mortality rates, preventing growth disorders, and enhancing immunological resilience. However, adherence to exclusive breastfeeding practices remains below the targeted level. This study aims to analyze the relationship between maternal characteristics, knowledge, and family support with the success of exclusive breastfeeding in infants. A cross-sectional design was used, conducted at the UPTD Sawang Health Center, South Aceh Regency, during February–March 2025. The population consisted of all mothers with infants aged 7–12 months visiting the health center, totaling 120 individuals. A sample of 97 respondents was selected using purposive sampling. Data were collected through a structured questionnaire, followed by data processing that included response completeness checks, variable coding, and data entry. Data analysis comprised univariate analysis to present the frequency distribution of maternal characteristics and knowledge, and bivariate analysis using the Chi-Square (χ²) test with a significance level of α=0.05 to test the hypotheses. The results showed that maternal employment was significantly associated with the success of exclusive breastfeeding (p < 0.001), whereas maternal education (p = 0.566), income (p = 0.915), maternal knowledge (p = 0.351), and family support (p = 0.252) were not significantly related. In conclusion, maternal employment has a significant relationship with exclusive breastfeeding success